The impact of EU conditionality on democratisation in Turkey: institutional transformation and policy (re)formation of minority rights, freedom of expression, the military and the judiciary - Özkurt, Fatma Zeynep (2013)
This thesis focuses on the impact of EU conditionality on democratisation in Turkey. Built on the assumption that Turkey's democratisation process cannot be fully understood without taking the EU's Impact into account, this thesis argues that even if external actors (e.g., the EU) can create opportunities for domestic political change In target states (e.g., Turkey), these actors cannot impose democracy externally; instead, they can provide support, or encourage power holders towards a more open and democratic system. Ultimately, however, these efforts cannot produce democratisation unless there are sufficient pro-democracy pressures at the domestic level. Empirically, the study examines institutional transformation and policy (re)formation in Turkey in the course of Its EUaccession process by conducting cross-sectoral and cross-temporal analysis. The analysis involves four policy areas and three time periods. These areas include minority rights, freedom of expression, the military and the judiciary; the domestic changes in these policy areas are traced across three time periods: 1999-2002, 2002-2004, and 2005-2008. The study is motivated by an academic interest in the intricacy of Turkey's long-term association with the EU and seeks to explore the external and internal dynamics of Turkey's candidacy process by employing theoretical tools offered by Europeanisation research. Following a Europeanisation theoretical framework, as devised out of new institutionalist theories, the thesis traces and analyses the democratisation process of Turkey and examines Turkey's pre-accession process at two levels. It first looks Into EU-Ievel factors to explore how the EU influences domestic change In Turkey with respect to its conditionality strategy and influence mechanisms; and secondly, it examines the domestic factors that pertain to each policy area to assess how EU conditionality is translated into domestic policy responses. Drawing upon data derived from primary and secondary sources, the thesis has three main findings. First, the recent reforms in Turkey represent a substantively significant effort to consolidate Turkish democracy. Second, as the cross-sectoral analysis illustrates, Turkey's strong desire to accede to the EU played a triggering role in the institutional transformation and policy (re)formation of Turkey. Third, although EU conditionality greatly influenced the domestic political debate surrounding the recent political reforms, ultimately the internal political dynamics determined and shaped the policy outcomes in Turkey. The research also reveals that to fully understand the impact of EU conditionality on domestic change in Turkey, we need to draw on both the external incentives and the social learning models, since they explain different aspects of domestic change based on diverging international and domestic level factors. As a wider outlook, the thesis reflects on the role of international organisations in democracy promotion, relating it to wider academic debates on democratisation and Europeanisation and their implications for domestic transformations in target countries.